2009
DOI: 10.1001/archsurg.2009.60
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Glove Perforation and the Risk of Surgical Site Infection

Abstract: Without surgical antimicrobial prophylaxis, glove perforation increases the risk of SSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0
27

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(128 citation statements)
references
References 39 publications
1
100
0
27
Order By: Relevance
“…Glove perforations increase the risk of infection for both the surgical team and the patient [24][25][26][27]. This study is the first to demonstrate the incidence of glove perforation during revision TJA.…”
Section: Discussionmentioning
confidence: 66%
“…Glove perforations increase the risk of infection for both the surgical team and the patient [24][25][26][27]. This study is the first to demonstrate the incidence of glove perforation during revision TJA.…”
Section: Discussionmentioning
confidence: 66%
“…Another study by Harpaz et al also concluded that a surgeon may have transmitted hepatitis B to patients with perforated gloves as a probable cause [5]. Misteli et al found that the risk of surgical site infection (SSI) increases significantly in procedures in which gloves are perforated and microbial prophylaxis has not been administered [6]. It can be safely assumed that if reprocessed gloves with micro perforations are used, it may result in increasing the opportunity for transmission of infections from the patient to the treating team and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2,6]. Perforations can increase the risk of surgical-site infection, and expose the surgeon to blood-borne diseases such as HIV, hepatitis C virus, and hepatitis B virus [10,14]. Understanding the clinical situations in which perforations occur can aid the surgeon in taking steps to minimize the risk of infection to the patient and to minimize the risk of viral exposure to the surgeon.…”
Section: Introductionmentioning
confidence: 99%